COMPARATIVE ANALYSIS OF PUBLIC AND PRIVATE UNIVERSITY HEADS LEADERSHIP STYLES IN PUNJAB PAKISTAN - Tehmina Atta Gohar; Shehla Sheikh; Allah Noor Khan; Mazhar Gul; FazalIlahi Khan; Taj Muhammad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study was conducted to see the leadership styles of heads of public and private universities of Punjab, Pakistan. The primary objective of the study was to compare the leadership style of public and private university heads as perceived by teachers. The study was delimited to teachers as well as autocratic, democratic, and laissez-faire leadership styles. A quantitative research design and survey method were used for data collection. A sample of 372 teachers (270 public & 102 private) was taken by applying a simple random sampling technique. The data was collected by using a valid and reliable research instrument. The maximum data of the study were collected by the researcher herself whereas in some areas friends and relatives were consulted. The gathered data were analyzed by using the mean interpretation scale of Valdez (2020) and descriptive statistics mean and standard deviation as well. The study concluded that public university heads bear autocratic whereas private university heads bear democratic leadership styles. Similarly, the laissez-faire leadership style is not practicing as well as democratic and autocratic utilizing in both the university sectors.